Antimicrobial effect of essential oils against several pathogens and their influence on inhibition of salmonella enteritidis, listeria monocytogenes and staphylococcus aureus in paste of “alheira” during storage - Carvalho, Marta Isabel Pimenta de (2017)
Fermented meat products are part of the daily diet in rural areas of Portugal and have become very popular in urban centers. “Alheiras" are traditional, slightly smoked, naturally fermented meat sausages typical of the Northern regions (Trás-os-Montes) in Portugal. Essential oils (EOs), traditionally used as flavoring agents, have been revealing good antimicrobial properties, becoming a good natural alternative to the use of chemical preservatives. The aim of this study was to investigate the antimicrobial effect of some EOs against several pathogens and their influence on inhibition of Salmonella Enteritidis, Listeria monocytogenes and Staphylococcus aureus in “alheira” during storage. First, the in vitro antimicrobial effect of 23 EOs against 41 foodborne and spoilage microorganisms was screened by the disc diffusion assay method (21 Gram-positive bacteria, 18 Gram-negative bacteria and two yeasts). Then, the minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) was studied for the EOs that displayed a better antimicrobial activity (i.e. halo > 10 mm) by the Microtiter plate assay. The antimicrobial effect of different concentrations of oregano EO (the EO with the lower MIC) (4%, 1.5%, 0.5%, 0.195% and 0.0975%) was evaluated in paste of “alheira” against Salmonella Enteritidis, L. monocytogenes and St. aureus along 21 days of storage at 4 ºC. The pH, water activity values and lactic acid bacteria were also evaluated. At last, sensory assessment was performed. Results showed that antimicrobial activity was variable, according to EOs used and microorganism. In general, oregano and thyme were the essential oils that showed highest antimicrobial activity and anise, fennel, garlic and ginger were the EOs with lower activity. The lowest minimum inhibitory concentration (0.0244%) against L. innocua was observed for Oregano. Oregano and thyme also showed higher MICs, against all microorganisms. Utilization of oregano EO in paste of “alheira” along 21 days of storage at 4 ºC resulted in a natural strategy to improve its safety against S. Enteritidis, L. monocytogenes and St. aureus. Although, oregano EO possesses antibacterial properties in vitro, their utilization as food antimicrobial agents must be assessed in the food product, in particular in a complex matrix as “alheira”. The antibacterial effect varies according to the oregano EO concentration and pathogen used. The results showed that 4% and 1.5% of oregano EO demonstrated the best antimicrobial activity against all the pathogens tested. 0.5% was able to result in ~ 2 log reduction for S. Enteritidis, whereas the lowest concentrations used (0.195% and 0.0975%) resulted in ~ 2-3 log reduction after 21 days Fermented meat products are part of the daily diet in rural areas of Portugal and have become very popular in urban centers. “Alheiras" are traditional, slightly smoked, naturally fermented meat sausages typical of the Northern regions (Trás-os-Montes) in Portugal. Essential oils (EOs), traditionally used as flavoring agents, have been revealing good antimicrobial properties, becoming a good natural alternative to the use of chemical preservatives. The aim of this study was to investigate the antimicrobial effect of some EOs against several pathogens and their influence on inhibition of Salmonella Enteritidis, Listeria monocytogenes and Staphylococcus aureus in “alheira” during storage. First, the in vitro antimicrobial effect of 23 EOs against 41 foodborne and spoilage microorganisms was screened by the disc diffusion assay method (21 Gram-positive bacteria, 18 Gram-negative bacteria and two yeasts). Then, the minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) was studied for the EOs that displayed a better antimicrobial activity (i.e. halo > 10 mm) by the Microtiter plate assay. The antimicrobial effect of different concentrations of oregano EO (the EO with the lower MIC) (4%, 1.5%, 0.5%, 0.195% and 0.0975%) was evaluated in paste of “alheira” against Salmonella Enteritidis, L. monocytogenes and St. aureus along 21 days of storage at 4 ºC. The pH, water activity values and lactic acid bacteria were also evaluated. At last, sensory assessment was performed. Results showed that antimicrobial activity was variable, according to EOs used and microorganism. In general, oregano and thyme were the essential oils that showed highest antimicrobial activity and anise, fennel, garlic and ginger were the EOs with lower activity. The lowest minimum inhibitory concentration (0.0244%) against L. innocua was observed for Oregano. Oregano and thyme also showed higher MICs, against all microorganisms. Utilization of oregano EO in paste of “alheira” along 21 days of storage at 4 ºC resulted in a natural strategy to improve its safety against S. Enteritidis, L. monocytogenes and St. aureus. Although, oregano EO possesses antibacterial properties in vitro, their utilization as food antimicrobial agents must be assessed in the food product, in particular in a complex matrix as “alheira”. The antibacterial effect varies according to the oregano EO concentration and pathogen used. The results showed that 4% and 1.5% of oregano EO demonstrated the best antimicrobial activity against all the pathogens tested. 0.5% was able to result in ~ 2 log reduction for S. Enteritidis, whereas the lowest concentrations used (0.195% and 0.0975%) resulted in ~ 2-3 log reduction after 21 days